Peran Advokat dalam Penegakan Hukum di Organisasi Asosiasi Advokat Indonesia Cabang Medan - Adelita Lubis (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2014)
This paper aims to determine the role of the Advocate in Law Enforcement and to identify constraints faced in enforcing the law, especially in defending a client in Medan Regional Government. Government lawyers in Medan in particular the Organization of the Indonesian Advocates Association (AAI) Medan Branch was instrumental in law enforcement, and is part of the Chess House of Law Enforcement consisting of police, prosecutors and judges. Advocates also defined in the Act No. 18 Year 2003 concerning Advocates increasingly providing high integrity and respect for the legal profession. Although in running role as an advocate there are constraints faced by such clients who are not able to give evidence in court proceedings, so the influence of the Mafia, clashed with police, and costs without cost that is often not up to the people who need no adverse effect advocates in their role as a law enforcer. Therefore, in this case it was clear that the Advocate has been carrying out its role well in accordance with the rules of the applicable law.